Newcastle disease virus suppresses antigen presentation via inhibiting IL-12 expression in dendritic cells - Nan, Fulong; Nan, Wenlong; Yan, Xin; Wang, Hui; Jiang, Shasha; Zhang, Shuyun; Yu, Zhongjie; Zhang, Xianjuan; Liu, Fengjun; Li, Jun; Zhou, Xiaoqiong; Niu, Delei; et al. (Journal of Zhejiang University. B. Science, 2024)
As a potential vectored vaccine, Newcastle disease virus (NDV) has been subject to various studies for vaccine development, while relatively little research has outlined the immunomodulatory effect of the virus in antigen presentation. To elucidate the key inhibitory factor in regulating the interaction of infected dendritic cells (DCs) and T cells, DCs were pretreated with the NDV vaccine strain LaSota as an inhibitor and stimulated with lipopolysaccharide (LPS) for further detection by enzyme-linked immunosorbent assay (ELISA), flow cytometry, immunoblotting, and quantitative real-time polymerase chain reaction (qRT-PCR). The results revealed that NDV infection resulted in the inhibition of interleukin (IL)-12p40 in DCs through a p38 mitogen-activated protein kinase (MAPK)-dependent manner, thus inhibiting the synthesis of IL-12p70, leading to the reduction in T cell proliferation and the secretion of interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), and IL-6 induced by DCs. Consequently, downregulated cytokines accelerated the infection and viral transmission from DCs to T cells. Furthermore, several other strains of NDV also exhibited inhibitory activity. The current study reveals that NDV can modulate the intensity of the innate–adaptive immune cell crosstalk critically toward viral invasion improvement, highlighting a novel mechanism of virus-induced immunosuppression and providing new perspectives on the improvement of NDV-vectored vaccine.